Overexpression of Ras homologous C (RhoC) induces malignant transformation of hepatocytes in vitro and in nude mouse xenografts. - Shuli Xie (Public Library of Science (PLoS), 2013)
Ras homologous C (RhoC) is expressed in various cancers, including hepatocellular carcinoma (HCC). In this study, we first analyzed RhoC expression in 46 HCC tissue specimens and found that RhoC expression was significantly increased in HCC tissues compared to the adjacent normal liver tissues. Next, we investigated the role of RhoC in malignant transformation of normal hepatocytes. The HL7702 cell line was stably transfected with a RhoC expression vector and then subjected to cell proliferation, differentiation, colony formation, migration and invasion assays, as well as nude mouse xenograft assays. Gene expressions in these cells were determined using RT-PCR and Western blot. Overexpression of RhoC significantly promoted proliferation and anchorage-independent growth of HL7702 cells, but suppressed cell differentiation, as compared with the parental cells and the empty vector-transfected control cells. Moreover, RhoC overexpression induced migration and invasion of HL7702 cells in vitro. Molecularly, RhoC increased the expression of cell cycle-related genes, matrix metalloprotease 2 (MMP2), MMP9 and vascular endothelial growth factor (VEGF). In addition, RhoC-transfected cells formed tumors in nude mice, whereas vector-transfected HL7702 cells did not form any tumors in nude mice. This study demonstrated the role of RhoC overexpression in malignant transformation of normal human hepatocytes, suggesting that RhoC may function as an oncogene in hepatocytes.